Pengembangan Media Pembelajaran Berbasis Web Desain Wix Materi Bangun Ruang Matematika SD Kelas V - Suanah Suanah (Proceedings of The ICECRS, 2019)
Education has a major influence on the formation of character and human personality, so that the quality of human resources is determined by the level of education pursued by students. Elementary School Mathematics Lesson V in the perception of most students is still considered difficult because it is abstract with calculation formulas and must use logic to analyze it. The purpose of the study was to develop Wix web-based learning media design material for elementary class V Mathematics space. Research design was development research carried out based on 6 stages of the process namely concept, design, material collection, manufacture, testing and publication. The subject of the study consisted of media experts, material experts and sample classes consisting of 29 fifth grade students at SD 1 Babakan Elementary School in Parungkuda District. Data collection techniques were carried out through the media expert test questionnaire and material expert test and user response questionnaire conducted by students. The results of the development of instructional media are based on the assessment of media experts and material experts, namely the need for improvement for the scope of the material presented is more complete and more interactive to facilitate material search. The criteria for the assessment of product trial instruments carried out by students get an average score of facilitation aspects of 2.753, the attractiveness aspect is 2.697 and the benefit aspects of the product are 2.583 so that based on the assessment indicators the product is in good criteria.